Work Interference with Personal Life: A Moderation of Work Stress and Organizational Justice on Turnover Intention - I Gusti Ayu Made Asri Dwija Putri; Benedicta Prisilia Christi (International Journal of Economics Accounting and Management, 2024)
The turnover phenomenon in Public Accounting Firms is an important problem because auditors are the main capital for the company. Factors that influence turnover in companies are employee stress and organizational justice. Departing from resource conservation theory, a moderation model is proposed in which Work Interference with Personal Life (WIPL) is expected to strengthen the relationship between work stress and organizational justice on turnover intention. This study intends to investigate how work stress and organizational justice affect job change intentions, moderated by WIPL. The research targets auditors employed at Public Accounting Firms in Bali Province, utilizing a questionnaire distributed via Google Forms for data collection, and employing structural equation modeling with SmartPLS for analysis. The research respondents were 91 people from twenty Public Accounting Firms in Bali Province. Respondents in this study were dominated by women, with a final education level of a bachelor's degree, a junior auditor position, and a length of service of 1-3 years. The results of the research state that work stress has a positive effect on the desire to change auditors, which means that the higher the level of stress experienced by auditors, the higher their intention to change jobs. Organizational justice has a negative effect on the desire to change auditors, meaning that the higher the level of organizational justice felt by the auditor, the lower the intention to change jobs. This research also shows that WIPL influences the influence of work stress on the desire to change auditors, but WIPL does not influence the influence of organizational justice on the desire to change auditors.